Helium-3 Diffusion MR Imaging of the Human Lung over Multiple Time Scales - Mugler, John P. (2008)
RATIONALE AND OBJECTIVES: Diffusion MRI with hyperpolarized (3)He gas is a powerful technique for probing the characteristics of the lung microstructure. A key parameter for this technique is the diffusion time, which is the period during which the atoms are allowed to diffuse within the lung for measurement of the signal attenuation. The relationship between diffusion time and the length scales that can be explored is discussed, and representative, preliminary results are presented from ongoing studies of the human lung for diffusion times ranging from milliseconds to several seconds. MATERIALS AND METHODS: (3)He diffusion MR imaging of the human lung was performed on a 1.5T Siemens Sonata scanner. Using gradient-echo-based and stimulated-echo-based techniques for short and medium-to-long diffusion times, respectively, measurements were performed for times ranging from 2 ms to 6.5 s in two healthy subjects, a subject with sub-clinical chronic obstructive pulmonary disease and a subject with bronchopulmonary dysplasia. RESULTS: In healthy subjects, the apparent diffusion coefficient decreased by about 10-fold, from approximately 0.2 to 0.02 cm(2)/s, as the diffusion time increased from approximately 1 ms to 1 s. Results in subjects with disease suggest that measurements made at diffusion times substantially longer than 1 ms may provide improved sensitivity for detecting certain pathological changes in the lung microstructure. CONCLUSION: With appropriately designed pulse sequences it is possible to explore the diffusion of hyperpolarized (3)He in the human lung over more than a 1000-fold variation of the diffusion time. Such measurements provide a new opportunity for exploring and characterizing the microstructure of the healthy and diseased lung.